(untitled) (Journal of Social Sciences Review, 2023)
Studies have concentrated on numerous strategies and measures to curb the crime rate. Out of these, interventions via education are most promising as teaching children has a multiplier effect on crime reduction. Empirically there is a debate on the effect of education on the incidence of crime, and it is reasoned that education with opportunities, relevance, and ethics plays a decisive role in reducing crime. This study has used more comprehensive indicators and a robust distribution-free approach to estimate the effect of education on the crime rate. The contour plot of Quantile on Quantile regression helps assess each level of education quality on each level of the business cost of crime. This model does not require the assumption of normality and linearity of variables. This study points out that primary and science education reduces crime rates at low levels, while management studies and research help reduce crime at high levels. This study provides a robust assessment of how education may influence the cost of crime at their different corresponding levels. These estimates can help determine how the marginal effects will affect and change in response to the change in the cost of crime. This study is an instrument in for assessing the role of education on crime at each quantile data position.